ANALISIS EFISIENSI EFEKTIF HIGH PRESSURE HEATER (HPH) TIPE VERTIKAL U SHAPE DI PEMBANGKIT LISTRIK TENAGA UAP AMURANG UNIT 1 - Reind Junsupratyo; Frans P Sappu; Arwanto M Lakat (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2018)
Heat exchanger is a device that serves to move one fluid to another fluid. In general, fluids are used as cooling using ordinary water (Cooling Water), and hot media use steam heat as heaters (Superheated Steam). One type of heat exchanger that is widely used in power generation industries is the Shell and Tube Heat Exchangers. High Pressure Heater (HPH) is one example of a heat exchanger that is widely used in the power generation industry that serves as a feed water heater before entering the boiler. This research was conducted to determine the effective efficiency of High Pressure Heater (HPH) at Amurang Power Plant (PLTU) unit 1. This determination is based on operational data on June of 2017. Data used to calculate the effective efficiency of High Pressure Heater (HPH). The calculations use the Shell and Tube Heat Exchanger heat transfer method. The calculation results obtained the highest effective efficiency achieved is equal to 69.392% and the lowest effective efficiency of 64.023% with an average effective efficiency of 66.531% during the month of June 2017.Keywords : Heat Exchanger, High Pressure Heaters, Effective Efficiency